2020
DOI: 10.1039/d0ta05806h
|View full text |Cite
|
Sign up to set email alerts
|

Triboelectric effect of surface morphology controlled laser induced graphene

Abstract: Here, we studied the triboelectric properties of structurally controlled laser-induced graphene (LIG) to clarify the key factors for improving the energy harvesting performance. With a facile defocusing method, the LIG...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…Moreover, the surface engineering also distinctly enhances the durability of graphene electrodes, which plays a critical role for practical application. Choi et al 150 reported the triboelectrification characteristics of LIG in terms of the porous to fibrous structural morphology with the TENGs concept. They fabricated a general porous structured Laser Induced Graphene (denoted as LIG) TENGs with power density 3.9 mW m −2 .…”
Section: Graphene As Triboelectric Materials For Tengsmentioning
confidence: 99%
“…Moreover, the surface engineering also distinctly enhances the durability of graphene electrodes, which plays a critical role for practical application. Choi et al 150 reported the triboelectrification characteristics of LIG in terms of the porous to fibrous structural morphology with the TENGs concept. They fabricated a general porous structured Laser Induced Graphene (denoted as LIG) TENGs with power density 3.9 mW m −2 .…”
Section: Graphene As Triboelectric Materials For Tengsmentioning
confidence: 99%
“…Copyright 2014, American Chemical Society. Reproduced under terms of the CC‐BY license 14a . Copyright 2020, Choi et al Published by Royal Society of Chemistry.…”
Section: Interfacial Structuresmentioning
confidence: 99%
“…Furthermore, the output performance of TENG with a nanometer‐scale surface could be multiplied by introducing the gear‐like structure 123b . Surface etching such as laser surface patterning and water electrospray etching was proven to be an effective method to fabricate micro/nanostructured surfaces 14b,124 14D).…”
Section: Interfacial Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the electrostatic induction of materials by the external triboelectric effect has been actively studied to develop various energy generators and self-powered devices that have a simple structure, allow for facile fabrication, and are lightweight. 11–13 The fabrication of self-powered touch-free sensors (TFSs), which exploit the coupling characteristics between electrostatic induction and triboelectricity, largely relies on materials with a high dielectric constant because of the large spatial displacement between positive and negative charges on the surface. 14–16 Recent efforts led to the development of self-powered TFSs fabricated with an organic polymer.…”
Section: Introductionmentioning
confidence: 99%